Thermal imaging and deep optical and electrochemical study of C70 fullerene derivatives with thiophene, pyrrolidine or indene moieties along with electropolymerization with thiophene substituted imine: Blends with P3HT and PTB7. (10th September 2022) - Kaim, Andrzej; Piotrowski, Piotr; Zarębska, Kamila; Bogdanowicz, Krzysztof A.; Przybył, Wojciech; Kwak, Anna; Skompska, Magdalena; Gnida, Pawel; Schab-Balcerzak, Ewa; Iwan, Agnieszka
Abstract: Three C70 fullerene derivatives, namely, C70-BTB and C70-MTB with thiophene or C70-MTP thiophene and pyrrolidyne moieties were synthesized and compared with synthesized C70-IPH containing indene moieties. Moreover, C70-BTB was compared with C60-BTB to analyse in deep the influence of fullerene football and rugby balls on the selected opto-electrical properties of new fullerene derivatives. All fullerene derivatives were characterized theoretically by using both time-dependent and independent density functional theory with the Perdew-Burke-Ernzerhof and Becke-Lee, W. Yang, R.G. Parr. The energy levels of the highest occupied molecular orbitals (HOMOs) and the lowest unoccupied molecular orbitals (LUMOs) were calculated and compared with corresponding values determined experimentally by cyclic voltammetry (CV). It was found that the LUMOHOMO energy gaps determined by the DFT/B3LYP/6–31G(d) method agree very precisely with the corresponding values obtained in the CV experiments. For the first time a possibility of electropolymeryzation of C60-MTB C70-BTB, C70-MTB and C70-MTP with (E)-1-([2, 2′:5′, 2′'- terthiophen ]-5-yl)-N-{4-[4-(4- fluorophenyl )-1, 3- thiazol -2- yl ]phenyl}methanimine (PV-BLJ-SC14) was shown. All fullerene derivatives and blends with poly(3-hexylthiophene-2, 5-diyl) and poly(4, 8-bis[(2- ethylhexyl ) oxy ]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl-alt-3-fluoro-2-[(2- ethylhexyl ) carbonyl ]thieno[3, 4- b ]thiophene-4, 6-diyl) were investigated in deep by UV–Vis spectroscopy in the solution and as the solid layers together with photoluminescence spectra. Structural defects of created layers based on new fullerene derivatives were studied by atomic force microscopy and thermal imaging. To summarize, the investigated fullerene derivatives present much better electrical properties than widely used PC70 BM. Moreover, the indene and pyrrolidine modifications demonstrated the best stability (thermally and at passing current) and electrical performance for all tested modifications. Additionally, a possible molecule rearrangement was observed resulting in improvement of electric conductivity through the layer. Finally, simple bulk-heterojunction polymer solar cells were constructed based on new fullerene derivatives as acceptors.